Determinants of Customer Engagement and Its Implications on Marketing Performance at National Private Commercial Banks in Jabodetabek - Yusuf, M. Syafrudin; Limakrisna, Nandan; Muharam, Hari (jfpublisher, 2022)
This research was conducted to determine the effect of CRM capabilities, corporate image and pricing strategy on customer engagement and their impact on the marketing performance of national private commercial banks in DKI Jakarta simultaneously. This study aims to analyse the factors that influence the marketing performance of national private commercial banks in Jabodetabek. The type of research used in this research is causality research that wants to explain cause and effect relationships between research variables. The method used in this research is descriptive and verification. The unit of analysis in this research is the organization, called national private commercial bank in Jabodetabek, and the unit of observation is the Branch Manager or Relationship Manager who is involved in marketing activities for bank products and services, and is responsible for bank's marketing performance. The result of this research found that CRM capabilities, corporate image, pricing strategies and customer engagement is proven to have a positive and significant influence on marketing performance and customer engagement at National Private Commercial Bank in Jakarta and Jabodetabek.